Impact of Pacing Site on QRS Duration and Its Relationship to Hemodynamic Response in Cardiac Resynchronization Therapy for Congestive Heart Failure. (24th July 2014) - DERVAL, NICOLAS; BORDACHAR, PIERRE; LIM, HAN S.; SACHER, FREDERIC; PLOUX, SYLVAIN; LABORDERIE, JULIEN; STEENDIJK, PAUL; DEPLAGNE, ANTOINE; RITTER, PHILIPPE; GARRIGUE, STEPHANE; DENIS, ARNAUD; HOCINI, MÉLÈZE; et al.
Electrical Impact of the Left Ventricular Pacing Site in CRT Introduction Recent studies have demonstrated that left ventricular (LV) pacing site is a critical parameter in optimizing cardiac resynchronization therapy (CRT). The present study evaluates the effect of pacing from different LV locations on QRS duration (QRSd) and their relationship to acute hemodynamic response in congestive heart failure patients. Methods and Results Thirty‐five patients with nonischemic dilated cardiomyopathy and left bundle branch block referred for CRT device implantation were studied. Eleven predetermined LV pacing sites were systematically assessed in random order: epicardial: coronary sinus (CS); endocardial: basal and mid‐cavity (septal, anterior, lateral, and inferior), apex, and the endocardial site facing the CS pacing site. For each patient QRSd and +dP/dtmax during baseline (AAI) and DDD LV pacing at 2 atrioventricular delays were compared. Response to CRT was significantly better in patients with wider baseline QRSd (≥150 milliseconds). Hemodynamic response was inversely correlated to increase of QRSd during LV pacing (short atrioventricular [AV] delay: r = 0.44, P < 0.001; long AV delay: r = 0.59, P < 0.001). Compared to baseline, LV pacing at the site of shortest QRSd significantly improved +dP/dtmax (+18 ± 25%, P < 0.001) but was not superior to other conventional strategy (lateral wall, CS pacing, and echo‐guided) and was inferior to a hemodynamically guided strategy. Conclusions In our study, we have demonstrated that changes of QRSd during LV pacing correlated with acute hemodynamic response and that LV pacing location was a primary determinant of paced QRSd. Although QRSd did not predict the maximum hemodynamic response, our results confirm the link between electrical activation and hemodynamic response of the LV during CRT.